IMPROVING STUDENTS READING COMPREHENSION ON HORTATORY EXPOSITION TEXT THROUGH RECIPROCAL TEACHING STRATEGY - Mustofa, Habib Ahmad Bisri; Apriliaswati, Rahayu; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract : This study wasClassroom Action Research (CAR) to improve senior high school students readingcomprehension. In this project, Reciprocal Teaching Strategy (RTS) was used tohelp students find meaning in English reading texts. The process of RTScomprises of reading activities such as predicting, questioning, clarifying,and summarizing which typically involving interaction between students-studentsand students-teacher. Predicting helped the students hypothesized the generalidea of the text. Questioning helped the students get deeper understanding ofthe text by generating questions. The students clarified unfamiliar parts inorder to understand the clumsy part of the text. Summarizing monitored thestudents understanding by concluding the text. After three cycles of theteaching learning processes, the students reading comprehension improvedgradually. Key words: Reciprocal Teaching Strategy, CAR, Reading Comprehension.